Hello, Mina? Regina Vanette Paredes Mendoza ; Rob Rownd, adviser. - Mendoza, Regina Vanette Paredes 1996- (2018)
"Hello Mina?, is a short psychological horror about Mina and her struggles as she tries to figure out her thoughts of violence towards herself and her imaginary friend. Mina is at a constant state of confusion in rationalizing her own thoughts as she tiptoes towards trying to seek help from her family. The film explores the struggles of people with mental health issues calling out for help, especially in an environment that dismissed possible mental health issues as drama or just a phase to endure. The Cognitive Triad theory by Aaron beck demonstrates the cycle of negative thoughts that people with depression undergoes. He illustrates that negative thoughts can lead to automatic thoughts of negativity then emotions then actions and cycling back to more thoughts of negativity. Thus, there is a need for that person to break the cycle. However, breaking the cycle can be made difficult by an environment that stigmatizes mental health issues. The Social Stigma theory by Ervin Goffman, considers mental health issues as one of the possible stigmas in the society that may in turn cause those suffering from mental health disorders to stigmatize themselves, making it harder for them to seek out help."